Fetal Anomalies in Obstetric Ultrasound in Enugu, Southeast Nigeria - Salome N. Ezeofor; Augustine C. Onuh; Chiamaka V. Uzochukwu (International Journal of Medicine and Health Development, 2025)
Background: Fetal anomaly (FA) is a global issue with varying degrees of morbidity and mortality. Objectives: To evaluate the various ultrasound-detected FA and their incidence in our environment and ascertain the maternal age group with the highest incidence. Materials and Methods: Obstetric ultrasound reports of 2217 patients aged 17–53 years with a gestational age (GA) of 13 weeks and above, who presented in the imaging departments of two busy specialist hospitals in Enugu from January 1, 2022, to December 31, 2023, were retrospectively analyzed for FA. Versana Premier GE systems were used for the ultrasound scan in both sites. Results: The highest incidence of anomalies was seen in mothers in the 30–34 age group. The central nervous system (CNS) was most affected at 42.3%, the genitourinary system (GUS) at 26.9%, the skeletal system (SS) at 23.1%, the gastrointestinal system (GIT) at 15.4%, and the cardiovascular system at 3.8%. In the CNS, the most frequent finding was hydrocephalus. Features of the presence of posterior urethral valve and achondroplasia were most frequent in the GUS and SS, respectively. Features of duodenal atresia were seen most in the GIT. Of the fetuses with anomalies, 11.5% of them had associated abnormal amniotic fluid volume. Conclusion: Most common fetal anomaly in the study population is in the CNS, with hydrocephalus being the most prevalent. The invaluable role of ultrasound in prenatal diagnosis, enabling better planning of delivery and postnatal care, cannot be overemphasized.